2021
DOI: 10.3390/su13052896
|View full text |Cite
|
Sign up to set email alerts
|

African Leafy Vegetables for Improved Human Nutrition and Food System Resilience in Southern Africa: A Scoping Review

Abstract: The economic potential of African leafy vegetables (ALVs) remains obscured by a poorly developed value chain. This scoping review assembled and examined scattered knowledge generated on ALVs across southern Africa, focusing on production, processing, marketing, and consumption. Two electronic databases (Scopus and Web of Science) were screened, and a total of 71 relevant studies were included and evaluated. The review provides a state of the art on knowledge related to utilisation of ALVs across the entire val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…Depending on the food type being processed, these techniques include boiling and drying of vegetables and grains (Masarirambi et al , 2010; Ibnouf, 2012); sun-drying, frying, boiling and roasting of insects (Niassy et al , 2016); and fermentation of milk, fruits and vegetables (Oguntoyinb et al , 2016; Agyei et al , 2020). The processing of vegetables through a combination of boiling and sun-drying is a prevalent practice reported in Swaziland (Masarirambi et al , 2010), South Africa (Masekoameng and Molotja, 2019), Sudan (Ibnouf, 2012), Kenya (Ayua et al , 2016; Gogo et al , 2016), Tanzania (Weinberger and Swai, 2006), Benin (Madode et al , 2011) and in most African countries (Shayanowako et al , 2021). The methods used for processing of wild fruit trees are also widely documented.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Depending on the food type being processed, these techniques include boiling and drying of vegetables and grains (Masarirambi et al , 2010; Ibnouf, 2012); sun-drying, frying, boiling and roasting of insects (Niassy et al , 2016); and fermentation of milk, fruits and vegetables (Oguntoyinb et al , 2016; Agyei et al , 2020). The processing of vegetables through a combination of boiling and sun-drying is a prevalent practice reported in Swaziland (Masarirambi et al , 2010), South Africa (Masekoameng and Molotja, 2019), Sudan (Ibnouf, 2012), Kenya (Ayua et al , 2016; Gogo et al , 2016), Tanzania (Weinberger and Swai, 2006), Benin (Madode et al , 2011) and in most African countries (Shayanowako et al , 2021). The methods used for processing of wild fruit trees are also widely documented.…”
Section: Resultsmentioning
confidence: 99%
“…For example, encroachment of human settlements and cultivated lands into woodlands and forests can lead to extermination of wild fruits. However, Shayanowako et al (2021) revealed that traditional food processing methods are still prominent in many African societies. The fears about the erosion of IK-based foods are likely to be addressed by the increasing consciousness of the health benefits that are associated with indigenous foods.…”
Section: Prospects and Challenges In Indigenous Knowledge Usementioning
confidence: 99%
See 2 more Smart Citations
“…The literature on food systems resilience has generally concentrated on the responses of food systems to climate change [ 7 , 8 , 9 , 10 ]; natural hazards [ 11 , 12 ]; socioeconomic crises, e.g., due to the COVID-19 pandemic [ 13 , 14 , 15 , 16 , 17 , 18 ]; and implications for interventions to build resilience [ 19 , 20 , 21 , 22 ]. There is a growing number of studies on food system resilience in rural and marginalized communities and neglected territories that focus on the role of natural resources [ 23 , 24 , 25 ]. Most of the studies on food systems resilience have focused on the measurement or assessment of livelihood, community resilience [ 26 , 27 , 28 , 29 , 30 , 31 ], determinants of livelihood resilience [ 20 , 32 , 33 ], and the linkages between sustainable agricultural practices and resilience [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%